An autoimmune disease risk SNP, rs2281808, in SIRPG is associated with reduced expression of SIRPγ and heightened effector state in human CD8 T-cells. Issue 1 (December 2018) - Sinha, Sushmita; Borcherding, Nicholas; Renavikar, Pranav; Crawford, Michael; Tsalikian, Eva; Tansey, Michael; Shivapour, Ezzatollah; Bittner, Frank; Kamholz, John; Olalde, Heena; Gibson, Emilee; Karandikar, Nitin
Abstract Multiple GWAS studies have shown that the SNP rs2281808 TT variant, present within theSIRPG gene, is associated with autoimmune diseases, such as type 1 diabetes. However, the role of SIRPγ in human T-cells is not known, neither is the functional significance of TT variant. Here we investigatedSIRPG genotypes and their effects on the fate and function of human T-cells. We found that the presence of T variant resulted in reduction of SIRPγ expression on T-cells. Functionally, SIRPγlow CD8 T-cells in CT and TT individuals existed in a heightened effector state with lower activation threshold and had greater expression of genes and molecules associated with migratory and cytotoxic potential. Further, SIRPγlow CD8 T-cells were deficient in transcription factors associated with long-term functional memory formation. Our study reveals biological consequences of the SNP rs2281808 and provides novel insights into the potential mechanisms by which SIRPγ might regulate human immune responses.